Design and evaluation of a parallel neighbor algorithm for the disjunctively constrained knapsack problem. (12th May 2016) - Quan, Zhe; Wu, Lei
Summary: We investigate the use of a parallel computing model for solving the disjunctively constrained knapsack problem. This parallel approach is based on a multi‐neighborhood search. In this approach, search threads asynchronously exchange information about the best solutions and use the information to guide the search. The performance of the proposed method was evaluated on the set of the standard benchmark instances. We show encouraging results and compare them to the state‐of‐the‐art solutions. Copyright © 2016 John Wiley & Sons, Ltd.